Experimental and theoretical study on the onset of nucleate boiling in non-uniform heating tube bundle channel. (March 2023) - Yan, Yiming; Wang, Meng; Fan, Guangming; Zeng, Xiaobo; Li, Zongkun
Highlights: Non-uniform heating tube bundle channel heat transfer experiments were conducted, and the ONB (Onset of Nucleate Boiling) data were obtained. The existing correlation can not predict the wall superheat at ONB quite well under non-uniform heating. The influence of Non-uniform heating on ONB has been theoretically analyzed. A new correlation for ONB under non-uniform heating is developed. Abstract: The transverse non-uniform heating tube bundle exists in steam generator and will affect the heat transfer and flow conditions in the shell side. It is important for the operational performance of the steam generator. In this study, a non-uniform heating tube bundle channel experimental device was set up. The channel consisted of two groups of heating tube bundles which were non-uniform heating in the transverse direction and uniform heating in the axial direction. Experiments and theoretical analysis were conducted to evaluate the influence of transverse non-uniform heating on the Onset of Nucleate Boiling (ONB). The locations of ONB during the experiments were determined from the heat transfer coefficient variations and the tube wall temperature variations. Experimental results at ONB were compared with existing well-known correlations under uniform heating conditions. And then under non-uniform heating conditions, the experimental wall superheat at ONB were furthermore compared with results predicted by the verified existing correlation. It was found that the correlation can't predict the experimental wall superheats well under transverse non-uniform heating conditions. Therefore, the influence of transverse non-uniform heating on ONB was theoretically analyzed. Correction factors were theoretically introduced and a new correlation was proposed. This new correlation was examined with experimental data and the result showed the correction factors need to be further studied.